GREEN CHEMISTRY APPLICATION FOR THE SYNTHESIS OF (1)-N-4’-METHOXYBENZYL-1,10-PHENANTHROLINIUM BROMIDE - Maulidan Firdaus; Jumina Jumina; Chairil Anwar (Indonesian Journal of Chemistry, 2008)
A simple, energy-efficient, and relatively quick synthetic procedure for the synthesis of (1)-N-4'-methoxybenzyl-1,10-phenanthrolinium bromide, based on green chemistry principles has been carried out. The synthesis was started by solvent-free reduction of p-anisaldehyde with NaBH4 to give 4-methoxybenzyl alcohol in 98% yield to be followed by solvent-free treatment of the resulted alcohol with PBr3 to yield 4-methoxybenzyl bromide (86%). Furthermore, the obtained bromide was reacted with 1,10-phenanthroline in acetone at reflux for 12 h to give the phenanthrolinium salt target in 68% yield.